Peranan Masyarakat Dalam Live In Di Desa Ngaduman Dusun Ngaduman - Aletta Dewi Maria; Ahmad Mansur; Enik Rahayu; Dyah Palupiningyas (FKIP, Universitas Palangka Raya, 2023)
The survey findings reveal that some have potential that can be developed into tourism and become worthy of being a leading tourist visit. The survey findings reveal that the problems in the field can be overcome by various stakeholders in making policies and synergizing with universities, especially STIEPARI Semarang in community service programs. That live in is a source of income for Ngaduman hamlet. Human resource development and training to improve the quality of tourism and institutional human resources (Pokdarwis)